THE REGULARITY OF INFLUENCE OF TRAFFIC PARAMETERS ON THE PROBABILITY OF REALISATION OF PLANNED PASSENGER TRANSFER AT TRANSFER NODES - G. Samchuk (Avtomobilʹnyj Transport (Harʹkov), 2017)
The article deals with the definition of traffic parameters that ensure the minimum value of the transfer waiting time for passengers. On the basis of experimental studies results, a regression equation to determine the probability of realisation of the planned transfer between a pair of vehicles was proposed. Using the identified regression equation, the transfer waiting time can be assessed for any headway exceeding 7,5 min.